Effects of Light Intensity and Irrigation Method on Growth, Quality, and Anthocyanin Content of Red Oak Lettuce (Lactuca sativa var. cripspa L.) Cultivated in a Plant Factory with Artificial Lighting - Thanit Ruangsangaram; Pariyanuj Chulaka; Kriengkrai Mosaleeyanon; Panita Chutimanukul; Michiko Takagaki; Na Lu (Horticulturae)
Cultivating red oak lettuce in plant factories often encounters challenges in achieving the desired red leaf coloration. To make the leaves a pleasant red color, anthocyanins are key substances that need to be induced. This study aimed to evaluate the effects of increasing light intensity and irrigation methods on the growth and leaf color of red oak lettuce in a controlled environment. Two light intensities (300 and 400 µmol m−2 s−1) with white LEDs and two irrigation methods (circulating vs. non-circulating irrigation) were applied seven days before harvesting. The results indicated that plants grown with circulating irrigation exhibited significantly higher fresh and dry weights than those grown under non-circulating conditions, regardless of light intensity. When non-circulating irrigation was applied, shoot fresh weight decreased by approximately 22% on the harvesting day compared to the circulating treatments. Under the 400 µmol m−2 s−1 light intensity with non-circulating irrigation (400N-C), plants displayed the lowest lightness (L*) at 40.7, increased redness (a*) to −7.4, and reduced yellowness (b*) to 11.0. These changes in coloration were optimized by day 5 after treatment. Additionally, spectral indices, including normalized difference vegetation index and photochemical reflectance index, varied significantly among treatments. The 400N-C treatment also resulted in the highest anthocyanin content and antioxidant activity in red oak lettuce. These findings suggest that combining high light intensity with non-circulating irrigation before harvest can improve both the coloration and quality of red oak lettuce in plant factories with artificial lighting.